Native and Modified Oryza glaberrima Steud Starch Nanocrystals: Solid-state characterization and Anti-tumour drug release studies - Oluyemisi Adebowale Bamiro; Michael Ayodele Odeniyi; Richard Tettey Addo (British Journal of Pharmacy, 2021)
In a bid to explore new biodegradable sourced materials for drug delivery, Oryza glaberrima starch was extracted, modified, and characterized. Nanocrystalstarch (NS) and acetylated nanocrystal starch (ANS) were produced from the native starch (S). The physicochemical properties, scanning electron microscopy(SEM), X-ray diffraction (XRD), Differential scanning calorimetry (DSC) and Fourier Transform Infra-red spectroscopy (FTIR) were done. The loading and release studies of Doxorubicin-loaded starches were carried out. The density, solubility, swelling capacity, and hydration capacity of the starch increased after modification whereas the amylose content was reduced. SEM revealed no change in morphology with sizes of the starch granules to be 5-15µm and the shape to be polyhedral. Modification of the starch increased the percentage drug loading capacity (DLC) and loading efficiency (LE). The drug release kinetics of the Dox-loaded S and ANS was the first-order release, while Dox-loaded NS was Korsemeyer-Peppas model. Improvement in the physicochemical properties of the NS and ANS made them useful carriers to sustain and control drug release.